Macroeconomics determinants of stock market index in Malaysia - Suvarna Sree, Sellathurai (2021)
The main purpose of this research is to examine the relationship between macroeconomic variables and the stock market index in Malaysia. The macroeconomics variables consist of Interest Rate (IR), Inflation Rate (INF), Real Effective Exchange Rate (REER) and Crude Oil Price (CRU). There are 120 observation data collected on monthly basis obtained from Bank Negara Malaysia and World Bank from year 2011 to 2020 for each variable. In addition, for the review of methodology of framework the relationship between the variables is investigated by using Unit Root Test, Johansen–Juselius Cointegration test, VECM estimation, Granger Causality test, Impulse Response Function and Variance Decomposition. The findings show that there is cointegration between stock market and macroeconomic variables. The results indicates that inflation rate, real effective exchange rate, crude oil price seem to significantly affect the FBMKLCI, but interest rate is insignificant. These variables should be emphasized whenever thegovernment implements any policy instrument with regards to the stock market.